Keratocystic odontogenic tumor associated with impacted maxillary third molar extending to the antrum: A challenging diagnosis - Roozbeh Pahlevan; Farnaz Keyhanlou; Sahar Fazel; Fatemeh Shahsavari (Elsevier, 2019)
Keratocystic odontogenic tumor (KCOT), traditionally known as odontogenic keratocyst (OKC) is a benign intraosseous neoplasm of odontogenic origin with potential for aggressive and infiltrative behavior. Mandible is the most common site of occurrence, while maxillary antrum involvement has been reported as a rare finding. We present a case of KCOT driven from an impacted maxillary third molar, invading the entire right maxillary sinus and the orbital floor; initially misdiagnosed as a dentigerous cyst. The clinical, radiological, and histological aspects of this tumor and its treatment management are discussed. Keywords: Third molar tooth, Maxillary sinus, OKC, KCOT